Iodine Intake and Iodine Status in the Czech Republic - Past, Present, Future - Bílek, R (Physiological research, 2025)
The physical and chemical properties of iodine, the importance of iodine for human health, iodine deficiency in the world and in Europe, the cycle of iodine in nature, values of iodine concentration in urine describing iodine deficiency, and the adequate or excessive supply of iodine to the body are presented in the work. The iodine intake of pregnant and lactating women and the state of iodine intake of these women in the Czech Republic are discussed. The history of iodine deficiency as well as the first mentions of the role of iodine in the thyroid gland and the first mentions of iodine prophylaxis in the world are explained. The present section describes the activities in the Czech Republic since the end of the Second World War, which contributed to the elimination of the iodine deficiency, including the establishment of the Interdepartmental Commission for Solving Iodine Deficiency. Population and other studies carried out in this period, which were related to the issue of iodine supply, are described. It was recorded that officially since 2004, the Czech Republic is among the countries where iodine deficiency is not currently a general problem. The future part is based on the Krakow appeal to leaders, politicians, scientists and officials, but also to the general population, to support actions leading to the elimination of iodine deficiency in Europe.
Keywords: Iodine; jod; ženské pohlaví; Humans; Nutritional Status; Pregnancy; nutriční stav; Female; Czech Republic; těhotenství; lidé; Česká republika